Green R&D versus end-of-pipe emission abatement: A model of directed technical change - Michael Rauscher (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
The paper looks at a model of directed technical change in an environmental-economics context. Firms can do conventional or 'green' R&D or they can abate emissions at the end of pipe. The paper has two main foci. On the one hand, it investigates the impact of environmental regulation on the allocation of resources to conventional R&D, green R&D, and end-of-pipe abatement. On the other hand, it addresses the question whether stricter emission standards should be used to support green R&D and/or economic growth.
Keywords: Q55; O41; 330; economic growth and the environment; directed technical change; Umweltschutz; Umwelttechnik; Industrielle Forschung; Umweltökonomik; Wirtschaftswachstum; Umweltpolitik